Using the Language Environment Analysis (LENA) System to Investigate Language Input in Greek Speaking Children - Binos, Paris; Taxitari, Loukia (My University, 2023)
Chapter 15 Using the Language Environment Analysis (LENA) System to Investigate Language Input in Greek Speaking Children Paris Binos, Loukia Taxitari This study sought to assess the effectiveness of the Language Environment Analysis integrating wearable audio recording with automated voice analysis, within the context of Greek-speaking families, aiming to discern evolving patterns of child-directed speech in typically developing children. Audio data from children aged 6-46 months were recorded during home interactions. The LENA Pro software parameters like conversational turn count, child vocalizations, and adult word count. The findings underscored a pronounced duration of Silence-Background noise and Distant Sounds. Strong correlations also emerged between parental linguistic input, adult-child conversational exchanges, child vocalizations, and meaningful interactions between children and adults. An inverse association between electronic device engagement and child vocalizations was also observed. LENA demonstrates its power in effectively mapping non-English linguistic environments, such as Greek, offering invaluable insights to stakeholders on refining language inputs for optimal language development.